Testing the Significant Differences of Wreathed Hornbill (Rhyticeros undulatus) sampled from Sarawak and Kalimantan Borneo - Nur Dania, Haris (Universiti Malaysia Sarawak, (UNIMAS), 2017)
Hornbills are the trophy species and the icon of Borneo. Besides, they are the keystone species as they aid in seed dispersal in the forest. There are eight species of hornbills found in Borneo; one of them is the Wreathed Hornbill, Rhyticeros undulatus. Eight parameters of dried specimens from 33 individuals were measured from Sarawak Museum and Bogor Zoological Museum, West Java, Indonesia. The data were subjected to Discriminant Function Analysis (DFA) using SPSS Version 24.0 and were randomised with Randomisation Test by using R Software Version 3.3.0. script. Only two parameters which are the bill depth (BD) and tarsus (TR) were selected as the most discriminant function based on DF A. Bill depth and tarsus were randomised for 100, 1000, 10000 and 100000 times. There are significant differences between the morphometric parameters of the Bornean R. undulatus sampled from Sarawak and Kalimantan Borneo as the randomisation process increases due to the possibility of cryptic species formation.